Compact Cities and Consumption Growth, Evidence from Urban Households - Huynh Phuc Phan; Le Quoc Du; Van Kim Hoang (Lembaga Penelitian dan Ilmu Pengetahuan JEPIP, 2025)
Vietnam's rapid urbanization has produced a mosaic of urban spatial forms, from compact delta cities to strikingly elongated coastal provinces, raising the question of whether city morphology shapes household consumption behavior. This study provides empirical evidence on the impact of city shape compactness on household consumption in Vietnam, using nighttime light satellite data to construct four indices of city shape compactness for 63 provinces and municipalities. Micro-level data from the Vietnam Household Living Standards Survey (VHLSS) 2024 yield a sample of 21,247 urban households across 30 provinces. Instrumental variables are constructed from hypothetical circular expansion paths calibrated on historical population growth rates and topographic constraints, addressing endogeneity arising from omitted variables, reverse causation, and selection effects. The results indicate that higher city shape compactness induces higher household consumption primarily through two channels: expanding intra-city travel frequency and enhancing disposable income. A reduction of 1 km in the average intra-city transportation distance is associated with approximately 3.1 percent higher per capita consumption, and this effect is concentrated in food and housing expenditures. Households with middle-aged heads are more sensitive to changes in compactness than those with younger or older heads. Compact city shape does not alter households' marginal propensity to consume. These findings highlight the importance of integrated spatial planning and transportation infrastructure investment as instruments for boosting domestic consumption in Vietnam's rapidly urbanizing economy.